1987
DOI: 10.1172/jci112783
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of aldosterone and potassium on induction of potassium adaptation in rat kidney.

Abstract: We examined the independent effects of a high potassium diet and increased aldosterone levels on the development of renal potassium adaptation. This condition is defined by the increased ability of the kidneys to excrete an acute infusion of potassium. Rats were adrenalectomized (ADX) and received aldosterone at basal levels (0.5 Asg/100 g * d) or at high levels (2.0 ;g/100 go d) for 10 d. In each experimental group, animals received either a control diet or a high potassium diet. In ADX animals with basal ald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 34 publications
3
30
1
Order By: Relevance
“…Consistently, a recent meta-analysis revealed that patients with a combined inhibition of aldosterone and angiotensin II action develop much more frequent episodes of severe hyperkalemia than patients with inhibition of either MR or AT1-dependent signaling. 45 Consistent with previous studies on adrenalectomized rats, 3,21,46 aldosterone-independent mechanisms cannot fully compensate for the loss of aldosterone. On a 5% K + diet, AS 2/2 mice but not AS +/+ mice decompensated, became hyperkalemic, and showed food avoidance.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Consistently, a recent meta-analysis revealed that patients with a combined inhibition of aldosterone and angiotensin II action develop much more frequent episodes of severe hyperkalemia than patients with inhibition of either MR or AT1-dependent signaling. 45 Consistent with previous studies on adrenalectomized rats, 3,21,46 aldosterone-independent mechanisms cannot fully compensate for the loss of aldosterone. On a 5% K + diet, AS 2/2 mice but not AS +/+ mice decompensated, became hyperkalemic, and showed food avoidance.…”
Section: Discussionsupporting
confidence: 86%
“…Our finding that the activation of renal secretory K + channels in response to K + intake does not require aldosterone is consistent with previous ion transport and electrophysiologic studies on isolated CDs from adrenalectomized animals. 19,21 Although previous studies did not show a reduced creatinine clearance in AS 2/2 mice at baseline, 33 we saw a slight, although not statistically different, trend for a lowered creatinine clearance in AS 2/2 mice on a 2% K + diet ( Figure 5). To what extent a possibly reduced GFR may have contributed to the decompensation of the AS 2/2 mice on the 5% K + diet is open.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…This form of metabolic alkalosis is usually secondary to mineralocorticoid excess and requires K depletion to produce maximal alkalinization ofthe extracellular fluid (21)(22)(23). Chronic hyperaldosteronism or exogenous mineralocorticoid therapy results in a three-to fourfold increase in K secretion in the cortical CD and initial collecting tubule (24)(25)(26), although effects on urinary K excretion are relatively minor (24). If net K secretion in the cortical CD and initial collecting tubule exceeds K intake, profound K depletion would ensue unless there were a compensatory increase in K-absorptive flux in more terminal nephron segments.…”
Section: Discussionmentioning
confidence: 99%